ANANALYSIS OF THE SOCIAL AND RELIGIOUS ROLES OF TUAN KADI SHELTER FOR THE MUSLIM COMMUNITY IN PEKANBARU CITY. - Afrinaldy Rustam; Ahmad Fauzi; Achmad Ghozai; Nurjanis; Nur Hilal Nazri Arif; M. Saidi Azuhar (Yayasan Wayan Marwan Pulungan, 2026)
This study examines the social and religious roles of Rumah Singgah Tuan Kadi as a faith-based shelter serving the Muslim community in Pekanbaru, Riau Province. Shelter homes (rumah singgah) function as important social institutions that provide assistance for individuals facing social, economic, and spiritual challenges, particularly travelers and marginalized groups. This research employs a qualitative descriptive approach to explore how Islamic values are integrated into the shelter’s social services and religious activities. Data were collected through participatory observation, in-depth interviews with administrators, beneficiaries, and community members, as well as document analysis conducted from November to December 2025. Data analysis followed the interactive model of Miles and Huberman, supported by source and method triangulation to ensure validity. The findings reveal that Rumah Singgah Tuan Kadi plays a significant social role by providing temporary accommodation, distributing social aid, and facilitating educational and community-based activities. In terms of religious function, the shelter offers regular religious studies, spiritual guidance, Qur’anic education, and moral development programs, particularly for children and adolescents. The community perceives the shelter positively due to its contribution to social welfare, spiritual growth, and community cohesion. Despite limitations in facilities, human resources, and funding, Rumah Singgah Tuan Kadi remains committed to fulfilling its socio-religious mission and strengthening social solidarity in an urban Islamic context.